Analysis of the Effect of Exchange Rate Profitability and Foreign Ownership on Transfer Pricing - Ista Ayu Oktafiana; Naila Najihah (Brilliant International Journal Of Management And Tourism, 2025)
This study aims to examine the effect of profitability, exchange rates, and foreign ownership on transfer pricing. The sampling method was purposive sampling and obtained 22 samples of companies that met the criteria. The data used were secondary data in the form of financial reports and annual reports of companies listed on the Indonesia Stock Exchange during the 2021-2023 period. The analytical method used in this study was multiple regression analysis. The results of this study indicate that (1) Profitability has a positive and significant effect on transfer pricing. This means that high profitability encourages companies to carry out transfer pricing by shifting profits. (2) Exchange rate has no effect on transfer pricing. This explains that the exchange rate is not one of the considerations for companies in carrying out transfer pricing. (3) Foreign ownership does not affect transfer pricing. High foreign ownership will tend to minimize the practice of transfer pricing to consider the risks that will be faced in the future, such as a decline in the company's value which will impact minority and majority shareholders.